Photographs, Manzanar, 1942-43 (1942)
Photograph of five family members shows Honey Toda in the middle of the back row [with brothers Roy Toda, left, and Akira Toda, right, and parents in front?] Inscription on back of photograph: ""May 1943, Toda family at Manzanar, California"".